Continuous theta burst stimulation in the treatment of epilepsia partialis continua: a case series - Chloé Algoet; Sofie Carrette; Alfred Meurs; Ann Mertens; Dimitri Hemelsoet; Paul Boon; Kristl Vonck (Bioelectronic Medicine)
Abstract Background Epilepsia partialis continua (EPC) is a medication-resistant form of focal status epilepticus (SE), causing significant morbidity. This case series explored whether continuous theta burst stimulation (cTBS) could reduce seizure activity in patients with EPC. Methods Three patients with motor EPC (2M/1F) underwent an accelerated cTBS protocol over four consecutive days (five 40-s trains/day, 5Hz bursts, 3 pulses at 50Hz/burst). Stimulation targeted the epileptogenic zone using a figure-of-eight coil at 80% of the resting motor threshold. Electroencephalography (EEG) was conducted before and after each session. Seizure frequency, intensity, adverse events (AEs), seizure diaries, and follow-up data were assessed. Results cTBS did not interrupt EPC in any patient. One patient reported a 17% reduction in seizure frequency. Another noted mild improvement in shoulder jerks, and a third reported reduced arm tension, though without clinical confirmation. EEG showed no significant changes. One patient experienced seizures during stimulation, and another reported worsening of pre-existing headaches. Conclusion In this small case series, a four-day accelerated cTBS protocol did not yield clinically meaningful seizure control in EPC. Further research is needed to evaluate TMS and TBS in SE and EPC, where a significant treatment gap remains.